The HOTS-Characteristic Diagnostic Tests Using the System Thinking Approach to Detect Acid-base Misconceptions in High School Chemistry - Septy Nur Fadhilah; Asih Widi Wisudawati (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2026)
Systems thinking is an approach to understanding the complex relationships between components in a system by combining analytical and systematic thinking. Misconceptions in the thinking process can hinder understanding of chemical concepts, so a diagnostic instrument that can comprehensively identify errors in thinking is needed. Many diagnostic instruments have been developed, but none have used a systems thinking approach. This study aims to develop a diagnostic test instrument based on the systems thinking approach with Higher Order Thinking Skill (HOTS) characteristics. The development follows Wilson's four-block model with a sequential exploratory mixed method, covering qualitative and quantitative stages. The instrument consists of 20 graded items covering four aspects of systems thinking: particle identification, component interaction, cause-and-effect relationships through calculation, and particle interaction inference. Validation shows a high Aiken V index from experts (0.91) and teachers (0.95), indicating content, construct, and language suitability. Student responses yielded an average NRS score of 75.8% (good category), with a note of time constraints. Rasch analysis showed good reliability (0.83) and lower person reliability (0.57) due to homogeneous responses on several basic items. Theoretically, this study confirms the importance of integrating HOTS and system thinking in the development of chemistry diagnostic instruments. The resulting instrument can be used by teachers as a formative assessment to detect students' misconceptions in depth and design more targeted learning interventions.